Serum levels of per- and polyfluoroalkylated substances and methylation of DNA from peripheral blood - Omichessan, Hanane; Dragic, Dzevka; Perduca, Vittorio; Truong, Thérèse; Polidoro, Silvia; Kvaskoff, Marina; Cano-Sancho, German; Antignac, Jean-Philippe; Baglietto, Laura; Mancini, Francesca Romana; Severi, Gianluca (Frontiers in Public Health, 2025)
BackgroundPerfluorooctanoic acid (PFOA) and Perfluorooctane sulfonate (PFOS) are among numerous chemicals in the Per- and polyfluoroalkylated substances (PFAS) group, which are commonly present in various consumer and industrial products. These chemicals are recognized for their persistency, the ability to accumulate in biological systems and their documented adverse effects on human health. Previous research, which has primarily centered on global methylation patterns, has suggested that some effects of PFAS on human health may be linked to modifications in DNA methylation (DNAm). The aim of our study was to assess the relationship between the serum levels of PFOS and PFOA and CpG site-specific methylation of DNA from peripheral blood.MethodsWe used a case–control study on breast cancer nested within the E3N cohort, a prospective study of French women, in which we measured DNAm at more than 850,000 CpG sites with the Illumina Infinium MethylationEPIC BeadChip for 166 case–control pairs. Serum levels of PFOS and PFOA were measured by liquid chromatography coupled to tandem mass spectrometry.ResultsWe found 64 CpG sites with significant hypomethylation or hypermethylation associated with increased levels of PFOA or PFOS (p-valueBonferroni < 0.05). The strongest association was found between PFOA serum levels and decreased DNAm at cg06874740 (p-valueBonferroni = 2.2×10−5) and between PFOS serum levels and decreased DNAm at cg02793158 (p-valueBonferroni = 9.3×10−5). Gene-set enrichment analyses using all CpG sites associated with PFOA or PFOS with an unadjusted p-value <0.01, identified 20 KEGG pathways for each of these compounds.ConclusionPFAS exposure may be linked to substantial and widespread changes in the methylome that may be involved in the consequences on health of these pollutants. Our findings indicate that the biological and health effects of PFOA and PFOS may be more intricate and varied than previously thought, reinforcing the need for policies aimed at regulating this class of endocrine-disrupting chemicals.